Spinal NGF Restores Opioid Sensitivity in Neuropathic Rats: Possible Role of NGF as a Regulator of CCK-Induced Anti-Opioid Effects. (1st March 2000) - Cahill, Catherine M; Coderre, Terence J
Abstract : The breadth of peripheral effects produced by nerve growth factor (NGF) in nociceptive processing has been well documented. However, less is known about the functional significance of central NGF in nociceptive transmission. The effect of NGF on the nervous system is dependent on the developmental stage. During the prenatal developmental period, NGF is critical for survival of nociceptors; in the postnatal period it regulates the expression of nociceptor phenotype, and in the adult it contributes to pain following an inflammatory insult. The implications for central NGF in the expression and regulation of spinal neuropeptides that are involved in pain mechanisms are reviewed. Knowledge has been gained by studies using peripheral nerve injury models that cause a deprivation of central NGF. These models also give rise to the development of pain syndromes, which encompass spontaneous pain, hyperalgesia and allodynia, routinely referred to as neuropathic pain. These models provide an approach for examining the contribution of central NGF to nociceptive transmission. Chronic pain emanating from a nerve injury is typically refractory to traditional analgesics such as opioids. Recent evidence suggests that supplementation of spinal NGF restores morphine-induced antinociception in an animal model of neuropathic pain. This effect appears to be mediated by alterations in spinal levels of cholecystokinin. The authors hypothesize that NGF is critical in maintaining neurochemical homeostasis in the spinal cord of nociceptive neurons, and that supplementation may be beneficial in restoring and/or maintaining opioid analgesia in chronic pain conditions resulting from traumatic nerve injury.